Comprendemos la multiplicación - Ortiz Arquinigo, Yesica (2019)
Through the development of this Learning Session it is intended to build in the student the daily practice of mathematics such as addition subtraction multiplication for the future._x000D_ The way in which students practice multiplication will be taken into account. As Keywords: Multiplication, Secondary Education, Solve quantity problems an activity that develops knowledge in this way, teaching children to stimulate practice and solve for pleasure practice the exercises like to practice the numbers motivate the child when he likes it and he is born” hoping that the objectives set will be achieved. And get them to like the area of mathematics one of the most important courses that is competent in our country where future students are competent, the achievement of the graduation profile of basic Education students is favored by the development of various competencies. _x000D_ Through the focus on Problem Solving, the Mathematics area promotes and facilitates students to develop the following skills:Solve quantity problems,Solve problems of form, movement and location, Solve problems of regularity, equivalence and change,Solves data management problems and uncertainty